Structural and signaling proteins in the Z-disk and their role in cardiomyopathies - Noureddine, Maya; Gehmlich, Katja (Frontiers in Physiology, 2023)
The sarcomere is the smallest functional unit of muscle contraction. It is delineated by a protein-rich structure known as the Z-disk, alternating with M-bands. The Z-disk anchors the actin-rich thin filaments and plays a crucial role in maintaining the mechanical stability of the cardiac muscle. A multitude of proteins interact with each other at the Z-disk and they regulate the mechanical properties of the thin filaments. Over the past two decades, the role of the Z-disk in cardiac muscle contraction has been assessed widely, however, the impact of genetic variants in Z-disk proteins has still not been fully elucidated. This review discusses the various Z-disk proteins (alpha-actinin, filamin C, titin, muscle LIM protein, telethonin, myopalladin, nebulette, and nexilin) and Z-disk-associated proteins (desmin, and obscurin) and their role in cardiac structural stability and intracellular signaling. This review further explores how genetic variants of Z-disk proteins are linked to inherited cardiac conditions termed cardiomyopathies.